Frequency of hepatitis C virus infection in patients with pediatric inflammatory bowel disease: a cross-sectional study - Sara Tarek; Ayman E. Eskander; Safa Meshaal; Eman Badr; Asmaa Abd El-Hakeem (SpringerOpen, 2023)
Abstract Background Patients with pediatric inflammatory bowel disease (PIBD) are believed to be at higher risk of hepatitis C virus (HCV) infection not only due to using of immunosuppressive drugs but also because of repeated blood transfusion and endoscopic and other invasive procedures used for diagnoses and effective controlling of the disease, so this study aimed to assess the frequency of HCV infection, in patients with PIBD at the New Children's Hospital, Cairo University, and identify the potential risk factors. Methods This cross-sectional analytic study included 165 IBD patients between 1 and 16 years old of both sexes who were attending the Pediatric Gastroenterology Clinic in the New Children's University Hospital, Cairo University. All patients were screened for anti-HCV antibodies using ELISA. Factors related to IBD (severity, modalities of the treatment, and invasive procedures), to infection (blood transfusion history and family history of hepatitis), and liver enzymes were registered. The risk factors were evaluated by multivariate logistic regression analysis. Results Present and/or past HCV infection was found in five (3%) of the IBD patients. The multivariate logistic regression to detect independent predictors of HCV +ve antibodies patients had statistically significant value with number of hospital admission related to IBD with p-value = 0.002, odd ratio (OR) = 1.467, and confidence interval (CI) = 95% (1.145-1.879) and with number of hospital admission unrelated to IBD with p-value = 0.024, OR = 0.750, and CI 95% (0.585-0.963). Conclusion The frequency of HCV infection in PIBD patients was 3%. Thus, the frequency of HCV infection in PIBD patients is similar to that in the normal population of the developing countries, and it is strongly related to hospital admission due to IBD or non-IBD causes.